2022
DOI: 10.3390/v14020219
|View full text |Cite
|
Sign up to set email alerts
|

Hyperendemic Dengue and Possible Zika Circulation in the Westernmost Region of the Indonesian Archipelago

Abstract: The transmission of dengue and other medically important mosquito-borne viruses in the westernmost region of Indonesia is not well described. We assessed dengue and Zika virus seroprevalence in Aceh province, the westernmost area of the Indonesian archipelago. Serum samples collected from 199 randomly sampled healthy residents of Aceh Jaya in 2017 were analyzed for neutralizing antibodies by plaque reduction neutralization test (PRNT). Almost all study participants (198/199; 99.5%) presented with multitypic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
3
0
1
Order By: Relevance
“…Despite a previous study reporting different cross-neutralization patterns observed in various ZIKV and DENV infections, whether a defined neutralizing antibody titer (PRNT 50 titer) can discriminate sDENV and DENV + ZIKV panels or it can be applied to regions where other flaviviruses (YFV, WNV or JEV) are prevalent remains unclear [ 62 ]. A recent study in Indonesian Archipelago, a DENV hyperendemic region, revealed multitypic neutralizing antibodies to two or more DENV serotypes and suggested possible ZIKV circulation based on high stringent PRNT 90 titers, underscoring the difficulty of using PRNT to delineate DENV and ZIKV infections in hyperendemic regions [ 63 ]. Other studies used two-step neutralization tests (initial screening by PRNT to ZIKV followed by PRNT to DENV1-4 and ZIKV) [ 51 , 52 ] or combination of IgG ELISA and neutralization test (for positive or equivocal samples) to investigate ZIKV or DENV seroprevalence in endemic regions [ 64-66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a previous study reporting different cross-neutralization patterns observed in various ZIKV and DENV infections, whether a defined neutralizing antibody titer (PRNT 50 titer) can discriminate sDENV and DENV + ZIKV panels or it can be applied to regions where other flaviviruses (YFV, WNV or JEV) are prevalent remains unclear [ 62 ]. A recent study in Indonesian Archipelago, a DENV hyperendemic region, revealed multitypic neutralizing antibodies to two or more DENV serotypes and suggested possible ZIKV circulation based on high stringent PRNT 90 titers, underscoring the difficulty of using PRNT to delineate DENV and ZIKV infections in hyperendemic regions [ 63 ]. Other studies used two-step neutralization tests (initial screening by PRNT to ZIKV followed by PRNT to DENV1-4 and ZIKV) [ 51 , 52 ] or combination of IgG ELISA and neutralization test (for positive or equivocal samples) to investigate ZIKV or DENV seroprevalence in endemic regions [ 64-66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a previous study reporting different cross-neutralization patterns observed in various ZIKV and DENV infections, whether a defined neutralizing antibody titer (PRNT50 titer) can discriminate sDENV and DENV+ZIKV panels or it can be applied to regions where other flaviviruses (YFV, WNV or JEV) are prevalent remains unclear [60]. A recent study in Indonesian Archipelago, a DENV hyperendemic region, revealed multitypic neutralizing antibodies to two or more DENV serotypes and suggested possible ZIKV circulation based on high stringent PRNT90 titers, underscoring the difficulty of using PRNT to delineate DENV and ZIKV infections in hyperendemic regions [61]. Other studies used two-step neutralization tests (initial screening by PRNT to ZIKV followed by PRNT to DENV1-4 and ZIKV) [48,49] or combination of IgG ELISA and neutralization test (for positive or equivocal samples) to investigate ZIKV or DENV seroprevalence in endemic regions [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…Zika virus infection has historically been a neglected viral infection in Africa, the Americas, Asia, and the Pacific, likely due to the prevalence of silent infections and relatively mild clinical manifestations 26 , 27 . Southeast Asian countries such as Thailand 28 , Cambodia 29 , 30 , Indonesia 31 , the Philippines 32 , India 33 , Singapore 34 , Japan 35 , and Vietnam 36 , 37 have experienced continuous circulation of ZIKV. Thailand, a geographically diverse country and popular tourist destination, has seen cases of ZIKV infection among travelers to various regions, including Japan 38 , Europe 39 , Israel 40 , and Canada 41 .…”
Section: Discussionmentioning
confidence: 99%